Synthesis of a 1, 4‐Bis[2‐(5‐thiophen‐2‐yl)‐1‐benzothiophene]‐2, 5‐dioctyloxybenzene Pentamer for Creatinine Detection. Issue 9 (23rd August 2021) - Hidayah Azeman, Nur; Asif Ahmad Khushaini, Muhammad; Daik, Rusli; Ismail, Ahmad Ghadafi; Yeop Majlis, Burhanuddin; Mat Salleh, Muhammad; Aziz, Tg Hasnan Tg Abdul; Bakar, Ahmad Ashrif A; Md Zain, Ahmad Rifqi; Teh, Chin‐Hoong
Abstract: The synthesis of novel material 1, 4‐bis[2‐(5‐thiophen‐2‐yl)‐1‐benzothiophene]‐2, 5‐dioctyloxybenzene pentamer (BOBzBT2 ) was carried out via Williamson etherification, bromination, and Suzuki coupling. Functionalization was carried out via the incorporation of dioctyloxy‐substituents on phenylene moiety to improve its solubility. The elongation of the π‐conjugation backbone was carried out through the addition of benzo[b]thiophene rings of BOBzBT2 to accelerate cation radicals′ formation. In FTIR, the disappearance of the stretching peak of υ(CBr) at 657 cm −1 confirms the coupling of benzo[b]thiophene rings end‐capped the BOBzBT2 UV‐visible shows the appearance of two broad bands at 343 nm and 422 nm, that related to π‐π* transition between thiophene and bithiophene groups with 2, 5‐bis(dioctyloxy)benzene moiety in the π‐conjugated backbone, respectively. DSC shows that the BOBzBT2 is a high purity compound. A gradual relaxation occurred between BOBzBT2 with creatinine as observed in UV‐visible analysis. It is expected that the BOBzBT2 sensed creatinine via NH−S and NH−O hydrogen bonding interactions. Abstract : A novel material of 1, 4‐bis[2‐(5‐thiophen‐2‐yl)‐1‐benzothiophene]‐2, 5‐dioctyloxybenzene pentamer (BOBzBT2 ) was synthesized. In FTIR, the disappearance of the stretching peak of υ(CBr) at 657 cm −1 confirms the coupling of benzo[b]thiophene rings end‐capped the BOBzBT2 . The appearance of two broad bands at 343 nm and 422 nm in UV‐visible is related to π–* transition between thiophene and bithiophene groups with 2, 5‐bis(dioctyloxy)benzene moiety in the π‐conjugated backbone, respectively. It is expected that the BOBzBT2 sensed creatinine via NH−S and NH−O hydrogen bonding interactions.